Analisis Kepuasan Mahasiswa Program Studi Informatika Terhadap Proses Pendidikan - Kartika, Luh Gede Surya; Saskara, I Putu Adi; Pratama, Putu Adi; Utama, Putu Kussa Laksana; Sanjaya, I Gede Wahyu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This study aims to analyze the level of student satisfaction with learning services at the Informatics Study Program of the State Hindu University (UHN) I Gusti Bagus Sugriwa Denpasar in the Odd Semester 2023/2024. The research method used was a survey with 42 respondents from the class of 2023. Data was collected through questionnaires that included aspects of the use of learning technology, the suitability of evaluation materials with course objectives, lecturers' interpersonal relationships, student involvement in research, and lecturers' mastery of cutting-edge issues. The results of the analysis showed that the aspects of the use of media and learning technology, the suitability of exam materials/assignments with course objectives, and the ability of lecturers to interact with students obtained the highest satisfaction score (4.43) and belonged to the category of